CLL2-BXX Phase II trials: sequential, targeted treatment for eradication of minimal residual disease in chronic lymphocytic leukemia. (21st February 2018) - Cramer, Paula; von Tresckow, Julia; Bahlo, Jasmin; Engelke, Anja; Langerbeins, Petra; Fink, Anna-Maria; Fischer, Kirsten; Wendtner, Clemens-Martin; Kreuzer, Karl-Anton; Stilgenbauer, Stephan; Böttcher, Sebastian; Eichhorst, Barbara; et al.
Aim: Four Phase II trials (clinical trials numbers: NCT02345863, NCT02401503, NCT02445131 and NCT02689141) evaluate a different combination of targeted agents in an all-comer population of approximately 60 patients with chronic lymphocytic leukemia irrespective of prior treatment, physical fitness and genetic risk factors. Patients with a higher tumor load start with a debulking treatment with bendamustine. The subsequent induction and maintenance treatment with an anti-CD20 antibody (obinutuzumab or ofatumumab) and a targeted oral agent (ibrutinib, idelalisib or venetoclax) are continued until achievement of a complete response and minimal residual disease negativity.Conclusion: This strategy represents a new era of chronic lymphocytic leukemia therapy where chemotherapy is increasingly replaced by targeted agents and treatment duration is tailored to the patient's individual tumor load and response. Lay abstract: Four Phase II trials evaluate a different combination of targeted agents in patients with chronic lymphocytic leukemia. Only patients with larger lymph nodes or higher lymphocyte counts receive chemotherapy in the beginning. Treatment with the novel agents is continued until no leukemic cells are detected (minimal residual disease negativity). Thus, chemotherapy is increasingly replaced by targeted agents and treatment duration is tailored to the patient's individual tumor load and the response achieved.